Meanders of the Kabodak River, Bangladesh: Meanders of the Kabodak River, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2023)
The study explores the meandering patterns of the Kabodak River and investigates the relationship among geometric aspects like sinuosity, width, amplitude, radius of curvature, and wavelength. The variables like basin area, river length, and longitudinal profile were measured, and the geometric aspects such as sinuosity, radius of curvature, meander wavelength, and meander amplitude were interpreted and calculated using Google Earth Pro and ArcGIS 10.5. With the aid of the software SPSS and unscrambler X, the relationship among the geometrical aspects was examined. Besides, different meander patterns have been identified by analyzing the meander form. The result reveals that the upper and lower parts of Kabodak appear more sinuous than the middle. Nodal patterns in river sections vary, with the upper and lower sections experiencing increased sinuosity due to lower gradients, reduced flow, and blockage. In contrast, the middle section exhibits less sinuous characteristics because of neotectonics upliftment. Among the variables, meander wavelength, amplitude, and radius of curvature have weak positive correlations between and among them, except for the wavelength-amplitude relation. The relationship between wavelength and amplitude is inversely proportional. The variable width appears non-responsive with other variables, which makes sense as the river's width is already structuralized due to human interference. Theoretically, the Kabodak River's meandering pattern deviated from other meandering river studies due to human interference. Similar types of work on other meander rivers of the delta may be explored to see if the result corroborates. Besides, the effect of human intervention on meandering patterns and morphological processes needs further study.J. Asiat. Soc. Bangladesh, Sci. 49(2): 149-164, December 2023